Recyclable Cytokines on Short and Injectable Polylactic Acid Fibers for Enhancing T‐Cell Function. (8th February 2019) - Shin, Hyun Mu; Ju, Youngjun; Kim, Gwanghun; Lee, Jae Won; Seo, Myung Won; Sim, Ji Hyun; Yang, Jusang; Noh, Sora; Kim, Jungbae; Kim, Hang‐Rae
Abstract: The current practice of cytokine‐based immunotherapy relies on high doses and multiple injections of cytokine agents, which raises patients' inconvenience and economic burden. Here, sustainable and recyclable cytokine delivery based on short and injectable polymer fibers immobilized with interleukin (IL)‐2 and IL‐15 is demonstrated, which can be retained at the target tumor sites upon injection. In detail, electrospun polylactic acid (PLA) fibers are treated with aqueous ethanol solution for their dispersion, increasing the interfiber space for highly efficient biomolecule conjugation, and further immobilized with protein G via enzymatic dopamine coating. The protein G‐immobilized PLA fibers are cut into short fibers using a microtome, and filtering is performed to collect injectable short PLA (sPLA) fibers with the lengths of 15–100 µm. These sPLA fibers are further loaded with cytokines via the interaction between protein G and Fc, and cytokine‐loaded sPLA (Cyto‐sPLA) fibers are injected near the tumor sites using a syringe. The administration of Cyto‐sPLA fibers efficiently suppresses the tumor growth up to 70% by reinvigorating nonfunctional T cells to a functional state that can kill tumors in a sustainable and recyclable manner. The injectable sPLA‐fiber platform can be employed as a carrier for the efficient delivery of various agents in vivo. Abstract : Cytokine‐immobilized short polylactic acid (PLA) fibers (Cyto‐sPLA) are injected to delivery cytokines, reinvigorating nonfunctional T cells. The administration of Cyto‐sPLA fibers efficiently suppresses tumor growth. Cyto‐sPLA fibers have great potential for the development of anticancer therapeutics, and the injectable sPLA‐fiber platform would make a versatile carrier of various agents to prolong their efficacy in vivo.